2017
DOI: 10.1016/j.jad.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of marijuana use among psychiatry patients with depression and its impact on recovery

Abstract: Background Depression is associated with substance-related problems that worsen depression-related disability. Marijuana is frequently used by those with depression, yet whether its use contributes to significant barriers to recovery in this population has been understudied. Method Participants were 307 psychiatry outpatients with depression; assessed at baseline, 3-, and 6-months on symptom (PHQ-9 and GAD-7), functioning (SF-12) and past-month marijuana use for a substance use intervention trial. Longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 15 publications
4
63
0
Order By: Relevance
“…Evidence suggests that efforts to selfmanage depression with cannabis are increasing [71][72][73][74][75] (also Aaron L. Sarvet, MPH, written communication, January 2, 2018) despite lack of evidence that cannabinoids are effective for this purpose 76,77 ; prospectively, cannabis worsens the course of depressive disorders. 78 The likelihood of treatment for depression is reduced in those with SUDs. 79 However, dual-focused treatment is more effective when 2 disorders are present.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that efforts to selfmanage depression with cannabis are increasing [71][72][73][74][75] (also Aaron L. Sarvet, MPH, written communication, January 2, 2018) despite lack of evidence that cannabinoids are effective for this purpose 76,77 ; prospectively, cannabis worsens the course of depressive disorders. 78 The likelihood of treatment for depression is reduced in those with SUDs. 79 However, dual-focused treatment is more effective when 2 disorders are present.…”
Section: Discussionmentioning
confidence: 99%
“…Study which assessed cannabis use among psychiatry outpatients with depression (at baseline and at 6 months of treatment), has shown that 40.7% of patients with depression used cannabis when assessed at baseline which then decreased significantly over 6 months of treatment. The study also revealed that cannabis has significantly Open Journal of Psychiatry worsened the symptoms of depression and led to poorer mental and physical functioning [9].…”
Section: Discussionmentioning
confidence: 89%
“…In addition, cannabis users with pre-existing depression may experience increased suicidal ideation [103], although conflicting findings showing no increase in suicidal ideation have also been reported [104]. Similar to the findings in individuals with pre-existing anxiety, cannabis use in patients with preexisting depression is associated with worse recovery of symptoms and outcomes [105].…”
Section: Association With Anxiety and Depressionmentioning
confidence: 85%